Dampak Penggunaan Facebook Terhadap Kepribadian Anak - Mutiawati Mutiawati (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2020)
The development of existing technologies, parents should immediately find the best way out so that the children are not too late in the advancement of existing technology. The benefits of social networking sites now have positive and negative impacts, which can build human resources development and can inhibit the development of a HUMAN resource, depending on who uses it and what it is used for. The family environment is the main environment in child personality formation. Parents ' role is very important for a child, so that children do not fall into the negative things that are inflicted